Clinical Indications of Recombinant Human Erythropoietin in a Single Center: A 10-Year Retrospective Study - Guan, Xiao-Zhen; Wang, Lei-Li; Pan, Xue; Liu, Li; Sun, Xiao-Lin; Zhang, Xiao-Juan; Wang, De-Qing; Yu, Yang (Frontiers in Pharmacology, 2020)
In the 1980s, recombinant human erythropoietin (rhEPO) began to be used in clinical practice. In this study, the clinical application of rhEPO from single-center in recent ten years was reviewed, and the scope of indications and clinical efficacy were evaluated.The medical records of 35829 in-patients who were treated with rhEPO in the first Medical Center of the Chinese PLA General Hospital from 2009 to 2018 were collected. According to the scope of indications approved by CFDA (China Food and Drug Administration), curative effect and off-label of rhEPO were analyzed. Of the 35829 patients, 19013 (53.1%) were male and 16816 (46.9%) were female, with an average age of (52.1 ±18.6) years. The usage of rhEPO is increasing year by year. The overall effective rate was 53.1%. The number of patients who met the indications accounted for 67.2%, and the effective rate patients with indications and Off-label were 48.8% and 50.7%. Among the patients with irregular use of rhEPO perioperative imperfect laboratory examination patients accounted for the highest proportion (7.1%). The volume of RBC(s)（red blood cell(s)） transfusion in patients with rhEPO was significantly less than that in patients without rhEPO (p<0.05). The use of rhEPO Off-label is very common and has a certain curative effect. It can be used as evidence support for the update of the scope of indications. In addition, There are still irregular use of rhEPO and transfusion in clinic. The unreasonable use of rhEPO and transfusion should be further standardized to ensure the safety and effectiveness.